Comparative analysis of active drag using the MAD system and an assisted towing method in front crawl swimming - Formosa, D. P.; Toussaint, H. M.; Mason, B. R.; Burkett, B. (Journal of Applied Biomechanics, 2012)
The measurement of active drag in swimming is a biomechanical challenge. This research compared two systems: (i) measuring active drag (MAD) and (ii) assisted towing method (ATM). Nine intermediate-level swimmers (19.7 ± 4.4 years) completed front crawl trials with both systems during one session. The mean (95% confidence interval) active drag for the two systems, at the same maximum speed of 1.68 m/s (1.40-1.87 m/s), was significantly different (p = .002) with a 55% variation in magnitude. The mean active drag was 82.3 N (74.0-90.6 N) for the MAD system and 148.3 N (127.5-169.1 N) for the ATM system. These differences were attributed to variations in swimming style within each measurement system. The inability to measure the early catch phase and kick, along with the fixed length and depth hand place requirement within the MAD system generated a different swimming technique, when compared with the more natural free swimming ATM protocol. A benefit of the MAD system was the measurement of active drag at various speeds. Conversely, the fixed towing speed of the ATM system allowed a natural self-selected arm stroke (plus kick) and the generation of an instantaneous force-time profile.